2015
DOI: 10.1007/s12282-015-0582-2
|View full text |Cite
|
Sign up to set email alerts
|

Z-11 trial and rethinking axillary reverse mapping

Abstract: Axillary lymph node dissection (ALND) was an integral part of the surgical procedure of breast cancer in the era of radical mastectomy. However, a randomized clinical trial has demonstrated that it does not reduce systemic recurrence or improve survival. Therefore, ALND was regarded as a surgical procedure for assessing nodal status and preventing axillary recurrence. Recently, sentinel lymph node (SLN) biopsy has become a standard method for assessing nodal status in breast cancer. Several randomized studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Noguchi et al had already demonstrated the presence of metastasis in axillary nodes identified by ARM. 10 In Nos et al, 14% metastatic involvement was reported in all patients who had a pN3 disease. 5 Most other studies were not taken into account as they had only N0 disease in their studies.…”
Section: Discussionmentioning
confidence: 93%
“…Noguchi et al had already demonstrated the presence of metastasis in axillary nodes identified by ARM. 10 In Nos et al, 14% metastatic involvement was reported in all patients who had a pN3 disease. 5 Most other studies were not taken into account as they had only N0 disease in their studies.…”
Section: Discussionmentioning
confidence: 93%